Analysis of fixation materials in micro-CT: It doesn’t always have to be styrofoam - Scherberich, Jan; Windfelder, Anton G.; Krombach, Gabriele A.; Justus Liebig University Giessen (My University, 2023)
Good fixation of filigree specimens for micro-CT examinations is often a challenge. Movement artefacts, over-radiation or even crushing of the specimen can easily occur. Since different specimens have different requirements, we scanned, analysed and compared 19 possible fixation materials under the same conditions in the micro-CT. We focused on radiodensity, porosity and reversibility of these fixation materials. Furthermore, we have made sure that all materials are cheap and easily available. The scans were performed with a Sky- Scan 1173 micro-CT. All dry fixation materials tested were punched into 5 mm diameter cylinders and clamped into 0.2 ml reaction vessels. A voxel size of 5.33 μm was achieved in a 180˚ scan in 0.3˚ steps. Ideally, fixation materials should not be visible in the reconstructed image, i.e., barely binarised. Besides common micro-CT fixation materials such as styrofoam (-935 Hounsfield Units) or Basotect foam (-943 Hounsfield Units), polyethylene air cushions (-944 Hounsfield Units), Micropor foam (-926 Hounsfield Units) and polyurethane foam, (-960 Hounsfield Units to -470 Hounsfield Units) have proved to be attractive alternatives. Furthermore, more radiopaque materials such as paraffin wax granulate (-640 Hounsfield Units) and epoxy resin (-190 Hounsfield Units) are also suitable as fixation materials. These materials often can be removed in the reconstructed image by segmentation. Sample fixations in the studies of recent years are almost all limited to fixation in Parafilm, Styrofoam, or Basotect foam if the fixation type is mentioned at all. However, these are not always useful, as styrofoam, for example, dissolves in some common media such as methylsalicylate. We show that micro-CT laboratories should be equipped with various fixation materials to achieve high-level image quality.
Keywords: ddc:610